Designing an Android Application to Reserve and Deliver Gas Cylinders to Homes Using the FierBase Database - Osman, Ikhlas Saleh; Salim, Hanan Abdulsalam; Al-Farjani, Salma Salem; Al-Qahwaji, Sanaa Mahmoud (The annual Scientific Conference for Under and Postgraduate Students at the University., 2024)
In light of the rapid development of technology and the widespread use of smartphones, there is an increasing reliance on electronic applications to facilitate the lives of citizens. The research problem includes the presence of excessive crowding from citizens when the company provides cooking gas cylinders, which sometimes results in citizens not taking gas cylinders fairly.This research aims to design an application to reserve cooking gas cylinders and deliver them to homes in the city of Zliten, Libya, and to organize the gas distribution process and reduce congestion that occurs in distribution warehouses, improve the efficiency of reservation and distribution, and provide accurate and easy-to-use services to citizens, in addition to using telephones. Smart in keeping up with technical developments. Through this research, an electronic application was designed that facilitates the reservation of cylinders through an easy-to-use interface, while providing continuous updates about the delivery processes to users and the company. The application also provides accurate options for delivery locations based on the user’s location. Given the clarity of the system requirements, the Waterfall Model methodology was used as an implementation model for the application, and the necessary data was collected from electronic and traditional sources Through this research, an electronic application was designed that facilitates the reservation of cylinders through an easy-to-use interface, while providing continuous updates about the delivery processes to users and the company. The application also provides accurate options for delivery locations based on the user’s location. Given the clarity of the system requirements, the Waterfall Model methodology was used as an implementation model for the application, and the necessary data was collected from electronic and traditional sources The Unified Modeling Language (UML) was used to analyze the system, and to design the system, the Android Studio program was used to build the application using both the Java and All the desired goals were achieved, and an easy-to-use application was built, devoid of complexity. The research also came up with many recommendations for adding the electronic payment feature and opening delivery outside the city of Zliten. Adding warehouses outside the city, adding an order tracking system, and the feature of obtaining the location path directly.